All That is Just Ersatz: The Meaning of Work in the Life of Immigrant Newcomers. (1st February 2013) - Roberman, Sveta
Abstract In this study, I present the case of middle‐age and late middle‐age Jewish immigrants from the former Soviet Union to Germany, who are attempting to rebuild their employment biographies and construct identities of social worth and status in the new country but are constrained from entering formal salaried jobs and are thus pushed into alternative work schemes. I explore the everyday experiences of these subjects and analyze why the alternative work projects fail to provide an equal substitute for formal salaried employment. Highlighting work as a crucial resource for the construction of immigrants' self‐perceptions, identities, and sense of belonging in a new country, I challenge claims about the diminishing meaning of work—in particular what is considered to be standard (long‐term, salaried) employment—in the construction of identities and determination of social hierarchies in contemporary Western societies. [unemployment–underemployment, nonstandard work, immigrant experience, recognition, marginalization]